2007
DOI: 10.2174/138945007779940160
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiology of Osteoarthritis: Pathomechanisms and Potential Therapeutic Targets

Abstract: Osteoarthritis, a degenerative joint disease, is the most disabling condition of the Western world. It affects first and foremost the articular cartilages and leads to a molecular and supramolecular destruction of the extracellular cartilage matrix. In addition, the cells, the chondrocytes, show severe alterations of their phenotype: they get anabolically and catabolically activated, change accordingly their gene expression pattern, lose their differentiated phenotype, and undergo focally cell death and cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 109 publications
(134 reference statements)
1
50
0
1
Order By: Relevance
“…The majority of chondrocytes in OA cartilage, however, are severely degenerated (15) and many are undergoing cell death or "chondroptosis" (16). It was recently demonstrated that OA cartilage is associated with a reduction and loss of regulators of the autophagy pathway (ULK, Beclin-1, and LC3 expression) and an increase in cell death (characterized by increased expression of PARP p85) (14).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of chondrocytes in OA cartilage, however, are severely degenerated (15) and many are undergoing cell death or "chondroptosis" (16). It was recently demonstrated that OA cartilage is associated with a reduction and loss of regulators of the autophagy pathway (ULK, Beclin-1, and LC3 expression) and an increase in cell death (characterized by increased expression of PARP p85) (14).…”
Section: Discussionmentioning
confidence: 99%
“…O steoarthritis (OA) 3 is the most common disorder affecting diarthrodial joints and has been associated with agerelated loss of homeostatic balance between degeneration and repair mechanisms. OA is often a consequence of abnormal mechanical forces that lead to altered metabolism in chondrocytes, the single cellular component in articular cartilage.…”
mentioning
confidence: 99%
“…OA is often a consequence of abnormal mechanical forces that lead to altered metabolism in chondrocytes, the single cellular component in articular cartilage. Although OA is generally classified as a noninflammatory disease, prominent proinflammatory mediators, including cytokines, PGs, and reactive oxygen species are believed to play pivotal roles in the disease pathogenesis (1)(2)(3)(4)(5)(6). It is increasingly appreciated that chondrocytes, like osteocytes in bone, function as mechanosensors by which local mechanical forces influence cellular metabolism.…”
mentioning
confidence: 99%
“…However, generally speaking, damage is repaired by chondrocytes in the subchondral bone plate or mesenchymal stem cells, inflammatory cells and cytokines in the bone marrow. Ultimately, damage is repaired by fibrous cartilage (Roach et al, 2007;Richter, 2009). From the histological staining results in the control group, we observed that the defects were filled with fibrous cartilage (Figs.…”
Section: Discussionmentioning
confidence: 89%